Examining of Certain Physical and Chemical Variables of Potable Water in Three Types of Home Stored Tanks in Baghdad - A. Al-Hiyaly, Sedik; A. Al-Tammemi, Jazaer; R. Khdaier, Saba (Iraqi Journal of Science, 2023)
Various types of storing tanks are used to store municipal water at homes. This study was carried out to examine several water physical and chemical variables such as pH, EC, TSS and TDS after different storing periods. The obtained results showed no significant differences between the mean of pH values which ranged from 7.27 ± 0.04 in a water sample of galvanized tank after six days of storing to 8.10 ± 0.12 in water sample of aluminum tank after nine storing days. In case of electric conductivity, Highest mean values (1.85±0.09 μS/cm and 1.44 ± 0.21μS/cm) were found in galvanized tank samples for different storing periods while the lowest mean values (0.58±0.06 μS/cm and 1.04±0.06 μS/cm) were recorded in aluminum tank samples. However in plastic tanks samples, the mean values were moderated (0.94 ±0.05 μS/cm and 1.16±0.03 μS/cm) between means of both tanks. In case of TSS, the current data have shown significant differences between mean values of examined stored water samples where highest values (730.0±31.97 mg/l - 1060.0±141.42 mg/l) were in galvanized tank water samples and the lowest mean values (27.67±21.36 mg/l – 118.33 ±18.46 mg/l) were in plastic tank water samples whilst in aluminum tank water samples, these values were varied from 193.33±10.66 mg/l – 253.33±22.2 mg/l). In general, only water samples stored in galvanized tank had mean value significantly higher that of control sample which had 251.33±3.21 mg/l. Regarding TDS, this study has found that highest mean values (800.0±40.0 mg/l – 1600.0±100.0 mg/l) were recorded in water samples of aluminum tank and the lowest mean values (40.0±10.0 mg/l – 120.0±10.0 mg/l) were found in water samples of plastic tank while water samples of galvanized tank had mean values varied from 680.0 ±10.0 mg/l – 1172.0 ±18.08 mg/l. Control sample, however had mean value of 495.0±5.0 mg/l which was only higher than that of plastic tank